2003
DOI: 10.1109/tcst.2003.813376
|View full text |Cite
|
Sign up to set email alerts
|

Set-point regulation of an anaerobic digestion process with bounded output feedback

Abstract: Abstract-This work addresses the robust output feedback tracking problem for a biological wastewater treatment process in the presence of input constraints and limited knowledge on the process parameters. The considered process is an anaerobic up-flow fixed bed biological reactor within a semi-industrial scale pilot plant for the treatment of industrial wine distillery wastewater. A mathematical model describing the dynamic behavior of the biological process is considered and nonlinear control techniques are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
57
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 26 publications
0
57
0
3
Order By: Relevance
“…The most popular ones are robust output feedback control [1][2][3] and adaptive control [4][5][6]. In [7], the authors have reviewed a number of control strategies for anaerobic digestion systems and have concluded that neither the classical nor the advanced control methods have succeeded in overcoming all the difficulties which arise in the efficient operation of these processes.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular ones are robust output feedback control [1][2][3] and adaptive control [4][5][6]. In [7], the authors have reviewed a number of control strategies for anaerobic digestion systems and have concluded that neither the classical nor the advanced control methods have succeeded in overcoming all the difficulties which arise in the efficient operation of these processes.…”
Section: Introductionmentioning
confidence: 99%
“…The (classical) output is the biomass growth (through gaseous production), the control is the dilution rate (see [22] for a review of control strategies). For scalar continuous output, there exists many approaches based on well-accepted models ( [7]), using constant or adaptive yield [18,3]. Some original approaches make use of a supplementary competitor biomass [20].…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic digestion is a process where microorganisms decompose the organic compounds into biogas (a gas mixture of methane and carbon dioxide). The process can also be adapted to wastewater treatment, because it reduces the chemical oxygen demand (COD) in the outlet stream below a specified value, usually fixed by environmental and safety rules, see e. g. [ 2,7,10 ].…”
mentioning
confidence: 99%
“…In this paper we consider a well known model of an anaerobic digestion process, based on two main reactions [ 2,7,8 ]: (a) acidogenesis, where the organic substrate (denoted by s 1 ) is degraded into volatile fatty acids (VFA, denoted by s 2 ) by acidogenic bacteria (x 1 ); (b) methanogenesis, where VFA are degraded into methane CH 4 and carbon dioxide CO 2 by methanogenic bacteria (x 2 ). The mass balance model in a continuously stirred bioreactor is described by the following nonlinear system of ordinary differential equations:…”
mentioning
confidence: 99%
See 1 more Smart Citation